Effects of Plyometric and Repeated Sprint Training on Physical Performance - Ivan Krakan; Luka Milanovic; Ivan Belcic (Sports, 2020)
The purpose of study was to resolve the effect of plyometric training and repeated sprint training on physical performance. The study was conducted on 41 subjects in two experimental groups (plyometric/repeated sprints training). Before and after the training program, subjects were subjected to diagnostic procedures that included standard test protocols. Results proved a statistically significant difference only after the plyometric training program compared to the repeated sprint group in countermovement jump (8.65% vs. 2.21%). In variable repeated jumps, an increased value was recorded (2.9% vs. 4.29%), like in sprint variables after the training program where certain trends of progress happened after the repeated sprint ability training and the specificity of the program (5 m = 0.89%, 10 m = 1.07% and 25 m = 1.35%), while plyometric training recorded unchanged values at 5 and 10 m, and a 0.27% improvement at 25 m. Stagnation of the 20-yard test was recorded in both groups. There was no difference between training programs in any variables of functional capacities, with similar measures recorded in repeated sprint ability. After six weeks of both training types, positive changes can be expected in explosive strength of lower extremities, increases in acceleration area, and maximum speed.